A 3D electrode of core@shell branched nanowire TiN@Ni0.27Co2.73O4 arrays for enhanced oxygen evolution reaction. (September 2018) - Wen, Wei; Chen, Yi-Na; Wang, Shu-Guang; Cao, Min-Hua; Yao, Jin-Cheng; Gu, Yi-Jie; Wu, Jin-Ming
Graphical abstract: Highlights: Ni-doped Co3 O4 nanosheets were deposited on TiN nanowires to construct a binder-free 3D electrode. Single-crystal-like TiN nanowires improve the conductivity of the electrode. The Ni-doped Co3 O4 nanosheets have a mesoporous structure with an ultrathin thickness. The obtained TiN@Ni0.27 Co2.73 O4 electrode shows high OER activity. Abstract: The combination of highly active materials with judicious nanostructures is crucial to develop high-performance electrocatalysts for oxygen evolution reaction (OER), which involves sluggish multistep electron transfer processes. Herein, TiN nanowire arrays are used as conductive trunks to support active Ni-doped Co3 O4 (Ni0.27 Co2.73 O4 ) nanosheets to construct a binder-free three-dimensional (3D) electrode for OER. In the core@shell configuration, the TiN nanowire arrays possess a single-crystal-like structure favoring charge migration and the ultrathin Ni0.27 Co2.73 O4 nanosheets have a mesoporous structure providing more active sites. The hierarchically branched morphology, high conductivity and large surface area can be achieved simultaneously by the optimization in composition and nanostructure, which contributes to excellent electrochemical performances. The TiN@Ni0.27 Co2.73 O4 electrode shows much better OER activity than the Ni-doped Co3 O4 nanosheets deposited on planar Ti substrate and low conductive TiO2 nanowire arrays.